Effect Of Dolomite Lime Dosage And Goat Manure Fertilizer Dosage On The Growth And Yield Of Tomato Plant (Lycopersicum esculentum MILL.) - Permono, Sigit; Sulistiyo Budi, Luluk; Rahayu, Sri; Pambudi Nurwantara, Ma'ruf (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study evaluated the interaction between dolomite lime and goat manure dosages on the growth and yield of tomato plants (Lycopersicum esculentum Mill.). The experiment was arranged in a factorial randomized block design with two factors and three replications. Dolomite lime was applied at four levels (0, 5, 10, and 15 g per polybag), while goat manure was applied at 0, 37.5, 75, and 112.5 g per polybag. Observations included soil pH, plant height, number of leaves, leaf area, number of branches, number of fruits per plant, and biomass parameters. Significant interactions between dolomite lime and goat manure were observed for leaf number at 36 and 43 days after transplanting (DAT), leaf area at 43 DAT, number of branches at 36 DAT, and number of fruits per plant at 57 DAT, whereas no interaction occurred for soil pH, plant height, or biomass variables. Dolomite lime improved soil chemical conditions by increasing soil pH, while goat manure enhanced vegetative growth through improved nutrient availability. Optimal combinations differed among parameters. Overall, integrated application of dolomite lime and goat manure effectively enhanced tomato growth and yield under acidic soil conditions.